Analisis Pengaruh Kualitas Pelayanan Kapal Nusa Jaya Abadi di Pelabuhan Padang BAI terhadap Kepuasan Penumpang - Kastini, Ni Wayan; Susilawati, Made; Srinadi, I Gusti Ayu (VISA: Journal of Vision and Ideas, 2025)
This research aims to obtain the significant influence of the dimensions of reliability, responsiveness, assurance, empathy, and tangibles as well as the influence of the service quality of the Nusa Jaya Abadi Ship on passenger satisfaction using structural equation modeling (SEM) analysis. The research used 200 data from a research questionnaire with respondents being Indonesian citizens who had crossed from Padang Bai Harbor to Nusa Penida or vice versa at least once. This research uses 2 latent variables, namely the service quality variable which consists of c, responsiveness, assurance, empathy, and tangibles and the passenger satisfaction variable with 40 calculated variables. The research results show that the dimensions of reliability, assurance, and tangibles have a significant effect on service quality. Meanwhile, the dimensions of responsiveness and empathy do not have a significant effect on service quality. The research results also show that the service quality of the Nusa Jaya Abadi Ship at Padang Bai Port, Karangasem has a significant effect on passenger satisfaction.